Chronological analysis of the physiological quality of diaspores of Myracrodruon urundeuva Fr. All. in semiarid regions - Azevedo, Aderdilania Iane Barbosa de; Silva, Givanildo Zildo da; Bruno, Riselane de Lucena Alcântara; Andrade, Alberício Pereira de; Cruz, José de Oliveira (Acta Scientiarum. Agronomy, 2018)
The objective of this study was to evaluate the physiological quality of diaspores from Myracrodruon urundeuva mother trees developing in the Cariri region of the state of Paraíba, Brazil. The seeds were collected during three consecutive years and from different areas of the Cariri region. The seed collection areas comprised two sites in the municipality of Boa Vista and one in the municipality of São João do Cariri. The diaspores had their water content determined and were submitted to the following tests: germination, seedling emergence, first count of germination and seedling emergence (within 5 days), and speed of germination and seedling emergence. The treatment means were compared using the deviance statistic. The collection years and collection areas were compared by the Tukey test at a 5% probability level. The comparison between mother trees was made through principal component analysis and cluster analysis. The detected variation in the quality of M. urundeuva diaspores is dependent on environmental conditions. The physiological quality of M. urundeuva diaspores varies according to mother tree, collection area and year. Mother trees of groups 1 and 2 are the most promising since they included representatives of all three areas and produced diaspores of high physiological quality.